Language Heritage Maintenance of Javanese Krama Inggil through Traditional Cultural Activities in Komering Putih Village - Putri, Devi Yandika; Rani Barokah; Novia Rohma Savitri; Subandowo, Dedy; Siagiyanto, Bambang Eko (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2025)
This study examines efforts to preserve Javanese krama inggil (KI) through traditional cultural activities in Komering Putih Village, amidst the challenges of its declining use in daily communication. Using a qualitative ethnographic approach, this study highlights the important role of activities such as wayang (W), campur sari (CS), and kitab kuning (KK) in maintaining the continued use of KI. The findings show that these cultural activities contribute significantly to the preservation of KI in formal and ceremonial contexts. Nonetheless, the younger generation (YG) tends to be limited in their everyday use of KI, preferring the informal ngoko (NG) variant. This research emphasizes the need for an integrated preservation strategy to bridge the use of KI in ceremonial contexts and everyday life, so that this language remains a dynamic element in Javanese cultural identity.